Development of TISERA Application in Physical Education Learning for Student with Hearing Impairment - Muhammad Anggi Sultanto; Rafly Ikhsanudin Al Afghani; Isma Afina Salsabila; Shofa Sofia Rohimat; Salsa Dilla Meisya; Mesa Rahmi Stephani (Universitas Pendidikan Indonesia, 2021)
Physical Education learning for students with hearing impairment faces obstacles and difficulties due to the COVID-19 pandemic. This study aimed to create a Physical Education learning application product to help students carry out movement tasks and increase their motivation in Physical Education learning. The method used was a quantitative method with a descriptive-analytical approach. The sampling process used was an accidental sampling technique involving 11 respondents. The results of the implementation carried out for five meetings on 11 fifth grade students with hearing impairment in a Special Schools, using quizzes in the application, showed increased learning. About 82% of parents reported that the application was helpful during online learning, while the student enthusiasm for learning increased by 73%. Student understanding of the material increased while learning increased by 82%. External factors affecting students in learning Physical Education included animation and score acquisition. The score acquisition affected the student motivation to gain the best score. The results of the TISERA application as learning media in Elementary Schools can increase the student understanding of Physical Education learning materials.